The Correlation Between Verbal Linguistic Intelligence and Writing Ability of the EFL Students at UIN Datokarama Palu - Lestari, Dewi; Dzakiah, Dzakiah; Zulfikri, Zulfikri (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
The research aimed to determine whether verbal-linguistic intelligence significantly influences students’ writing performance. Nineteen students from the TBIG 2 class of 2024 participated in the study. The students’ verbal-linguistic intelligence was measured using a questionnaire, while their writing scores were obtained from the course lecturer. The data were analyzed using the Pearson Product-Moment Correlation Coefficient with SPSS version 27. The analysis revealed a correlation coefficient (r) of 0.654 with a significance value (p) of 0.002. These results indicate a strong positive correlation, meaning students with higher verbal-linguistic intelligence tend to perform better in writing tasks. The findings support Gardner’s theory of Multiple Intelligences, emphasizing the contribution of verbal-linguistic intelligence to students’ language skills, particularly in expressing ideas effectively in written form. Based on the statistical evidence, the study concludes that verbal-linguistic intelligence has a significant correlation with the writing ability of EFL students at UIN Datokarama Palu.